The SAGE encyclopedia of theory in science, technology, engineering, and mathematics - Mattingly, James; Rumenapp, Joseph C., 1985- (Los Angeles, CA : SAGE Publications, Inc., 2023)
Theories are part and parcel of just about every human activity that involves knowing about the world and our place in it. In all areas of inquiry from the most mundane to the most esoteric and sophisticated, theorizing plays a fundamental role. What is true of our everyday existence is even more pervasive in more scholarly fields. How is thinking about the subject organized? What methods are used in moving a neophyte in a given subject matter into the position of a competent student of that subject? What, in short, is the prime repository and vehicle for the knowledge that has been acquired in any discipline over the course of its development? The answer is the theories that are used, produced, and promulgated by the practitioners of those disciplines. The SAGE Encyclopedia of Theory is a landmark work serving as something of a capstone to 10 prior SAGE encyclopedias that examined theory in specific social science disciplines (psychology, sociology, education, political science, etc.). Within the pages of this more general work, readers will learn about the complex decisions that are made when framing theory, what goes into constructing a powerful theory, why some theories change or fail, how theories reflect socio-historical moments in time and how - at their best - they form the foundations for exploring and unlocking the mysteries of the world around us. Key features include: Over 300 signed articles written by key figures across the social sciences spread across four comprehensive volumes Further Readings and Cross References conclude each article aiding readers further in their research A Reader's Guide organizes entries by broad themes. A Resource Guide takes readers to the next step in their research journeys by listing classic books in the field, key journals, associations, and websites.
Description based on XML content.
Includes index.
Keywords: Science -- Methodology; Technology -- Methodology; Engineering -- Methodology; Mathematics -- Methodology